Analysis of the Sedimentation Rate of the Pappa River on the Service Period of the Pamukkulu Reservoir in Kab. Takalar - Andi Muhammad Subhan Saiby; Nursamiah; Dharmaputra Paembonan; Aldy Usman (PT FORMOSA CENDEKIA GLOBAL, 2023)
One of the important things in planning a dam is sedimentation analysis. Without a good and thorough analysis at the planning stage, the sedimentation that occurs can cause problems when the reservoir is operational. Although not quickly and significantly in its effect on reservoir operations, excessive sedimentation can reduce the service life of the reservoir. By writing this article, we aim to analyze the sedimentation rate produced by the Pappa River and its effect on the service life of the Pamukkulu Reservoir, Kab. Takalar. The data we need in our research include Reservoir Topography data, Hydrological Data, Sediment Data, and Geological Data. After processing the data above using the USLE method, we get a sedimentation rate of 7.193 mm/year. With this sedimentation rate value, through our calculations we project that in the 50th year the resulting sedimentation will be 4,498,175.66 m³/year which is still below the previous planning calculation of 4,658,000 m³/year.